PROBLEMS OF BURNING CONTROL IN FLAME FURNACES FOR HEATING OF SLUGS BEFORE PUNCHING - A. A. Oznobishin (Литьë и металлургия)
The problem of guarantee of gas-air correlation at the example of flame brazing furnace of forging production with several burners, operating on different capacities, is examined.